Assessing Genomic Admixture between Cryptic Plutella Moth Species following Secondary Contact. (13th October 2018) - Ward, Christopher M; Baxter, Simon W
Abstract: Cryptic species are genetically distinct taxa without obvious variation in morphology and are occasionally discovered using molecular or sequence data sets of populations previously thought to be a single species. The world-wide Brassica pest, Plutella xylostella (diamondback moth), has been a problematic insect in Australia since 1882, yet a morphologically cryptic species with apparent endemism ( P. australiana ) was only recognized in 2013. Plutella xylostella and P. australiana are able to hybridize under laboratory conditions, and it was unknown whether introgression of adaptive traits could occur in the field to improve fitness and potentially increase pressure on agriculture. Phylogenetic reconstruction of 29 nuclear genomes confirmed P. xylostella and P. australiana are divergent, and molecular dating with 13 mitochondrial genes estimated a common Plutella ancestor 1.96 ± 0.175 Ma. Sympatric Australian populations and allopatric Hawaiian P. xylostella populations were used to test whether neutral or adaptive introgression had occurred between the two Australian species. We used three approaches to test for genomic admixture in empirical and simulated data sets including 1) the f3 statistic at the level of the population, 2) pairwise comparisons of Nei's absolute genetic divergence ( d XY ) between populations, and 3) changes in phylogenetic branch lengths between individuals across 50-kb genomic windows. These complementary approaches all supported reproductive isolation of the Plutella species in Australia, despite their ability to hybridize. Finally, we highlight the most divergent genomic regions between the two cryptic Plutella species and find they contain genes involved with processes including digestion, detoxification, and DNA binding.